Techniques and Sequence of Sketching in the Conceptual Phase of Automotive Design - Saiful Bahari, Bin Hj Mohd Yusoff; Sinin, Bin Hamdan; Zalina, Binti Ibrahim (Human Resource Management Academic Research Society (HRMARS), 2018)
This paper evaluates the techniques of sketching in the conceptual phase of automotive design among automotive designers. The research identifies sketch types used in conceptual stage and a distinction is made between Thumbnail Sketch, Rough Sketch and Concept Sketch and they portray different stages of sketching process in the conceptual phase. An investigation (sketching task evaluation) with 9 automotive professional designers was conducted to evaluate the sketching approaches. Video Observational Analysis was carried out concerning 9 aspects identified such as Medium Used, Left/Right Hand, Line Thickness, Sequence of Activity, Size and Types of Sketch Produced with the results documented and discussed. An early finding shows that 5 types of sketching approaches portray 5 different sequence techniques for early automotive design conceptual phase.